DESIGN OF SMART TRAFFIC LIGHT SYSTEM BASED ON INTERNET OF THINGS - MUHAMMAD AMIR AFIQ, MOHAMED (Universiti Malaysia Sarawak (UNIMAS), 2018)
Traffic light control systems are universally used to monitor and control the flow of the vehicles at the junctions. The function of the traffic light is to regulate the movement of the vehicles in the transportation route but the synchronization of multiple traffic system at certain junctions can caused complicated problem. The conventional traffic light does not handle variable flows approaching at the junctions. Traffic congestion is normally caused by the number of the vehicles that are too many on the road. This problem need innovation and efficient solution invader to address it. In this paper, the design of the smart traffic light system is proposed based the Internet of Thing (IoT). The system will provide full advantage for monitoring and controlling a congestion model based on the sensor reading. The sensors placed at each lane will give improvement in detecting the vehicles and increasing the accuracy in collecting the data. The data is gathered and send to the microcontroller which process the data and produce the output for the flow of the traffic light according density of the traffic at each lane. Density of the traffic is calculated by the algorithm that have various variables. This project will use Arduino as it microcontroller and the ultrasonic is used to detect the congestion. The data that have been collected will be sent to the cloud storage which is Thingspeak channel. The data that have gathered will be display in graph and table. The data is gather and send to the microcontroller which process the data and produce the output for the flow of the traffic light according density of the traffic at each lane. Density of the traffic is calculated by the algorithm that have various variables. The system will synchronize with Android Application, which can show the notification of alert system, level of traffic congestion and real-time sensors data for each junction. The level of congestion is taken from the infrared sensor through the traffic light system by the microcontroller and the data is kept in the cloud storage for use in homegrown and national development models and traffic estimation. The techniques used is the sensor will take a data on many cars, the length of the farthest vehicle from the sensor and traffic speed of each traffic flow. The data is used to find the time needed by the vehicles to go through by the green light